An Analysis of Code-Mixing in Chef Juna's Utterances in Masterchef Indonesia Season 5 - Luh Sri Susi Susanti; I Nyoman Adi Jaya Putra; I Made Suta Paramarta (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study investigates the types and functions of code-mixing used by Chef Juna in MasterChef Indonesia Season 5. The research was conducted to identify the structural forms of code-mixing and the communicative purposes behind their use in televised discourse. A descriptive qualitative method was employed, and the data consisted of 33 utterances containing code-mixing taken from selected video recordings of the program. The data were analyzed using Muysken’s typology of code-mixing and Leech’s theory of language functions. The findings show that only two types of code-mixing were found: insertion and alternation, with insertion as the most dominant type. In terms of function, expressive function appeared most frequently, followed by informative, directive, and phatic functions. No instances of congruent lexicalization or aesthetic function were identified. The results suggest that code-mixing in Chef Juna’s utterances was used strategically to express evaluation, deliver culinary information, give instructions, and maintain interaction. These findings contribute to sociolinguistic studies of multilingual communication in media discourse.